Cybercrime Lintas Negara ASEAN: Studi Kasus Perjudian Online Dalam Ancaman Keamanan Nasional di Indonesia - Zalia, St. Fatimah Azzahra Zalia (CV. Cendikiawan Muda Sriwijaya, 2025)
Online gambling has emerged as a significant transnational cybercrime threat in Southeast Asia, particularly affecting Indonesia's national security. This study explores how illegal online gambling networks exploit jurisdictional gaps, digital payment systems, and weak regional law enforcement coordination to operate across borders. The research focuses on three key areas: the evolving tactics of cross-border gambling operations, their economic and social impacts on Indonesian society, and the institutional challenges faced by ASEAN countries in addressing this issue. Using a mixed-methods approach that combines legal analysis, case studies, and policy evaluation, the study reveals that these criminal networks increasingly rely on cryptocurrency, offshore servers, and local affiliates to sustain their activities. Findings also show strong links between online gambling and other forms of transnational crime such as money laundering and organized crime. Moreover, it highlights how these activities undermine Indonesia’s digital sovereignty, drain billions of rupiah annually from the national economy, and contribute to rising social instability. The study concludes that effective countermeasures require stronger regional cooperation, including harmonized cybercrime laws, improved intelligence sharing, and enhanced technical capacities among ASEAN member states.